2019
DOI: 10.1093/ejcts/ezz054
|View full text |Cite
|
Sign up to set email alerts
|

A European study on decellularized homografts for pulmonary valve replacement: initial results from the prospective ESPOIR Trial and ESPOIR Registry data†

Abstract: OBJECTIVES Decellularized pulmonary homografts (DPH) have shown excellent results for pulmonary valve replacement. However, controlled multicentre studies are lacking to date. METHODS Prospective European multicentre trial evaluating DPH for pulmonary valve replacement. Matched comparison of DPH to bovine jugular vein (BJV) conduits and cryopreserved homografts (CH) considering patient age, type of heart defect and previous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…We have shown the absence of calcium in a DAH reoperation 4.5 years after implantation in an infant [ 9 ] and extensive in vivo recellularization with non-immunogenic recipient cells in decellularized pulmonary and aortic allografts [ 26 ]. Decellularized pulmonary homografts showed significantly higher freedom from reoperation at 10 years compared with cryopreserved pulmonary homografts and almost no early cellular immune response [ 10 , 27 ]. The promising initial clinical results for DAH [ 9 ] led to the initiation of prospective multicentre trial, whose early results are reported here.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown the absence of calcium in a DAH reoperation 4.5 years after implantation in an infant [ 9 ] and extensive in vivo recellularization with non-immunogenic recipient cells in decellularized pulmonary and aortic allografts [ 26 ]. Decellularized pulmonary homografts showed significantly higher freedom from reoperation at 10 years compared with cryopreserved pulmonary homografts and almost no early cellular immune response [ 10 , 27 ]. The promising initial clinical results for DAH [ 9 ] led to the initiation of prospective multicentre trial, whose early results are reported here.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment there is an interest regarding decellularized pulmonary valve, studies entering the translational phase. The on-going ESPOIR trial targeting patients aged 21.3 ± 14.4, aims to compare decellularized homografts to the current alternatives -the bovine jugular vein conduit -Contegra conduit (30) and cryopreserved homografts, their initial results from registry data showed their superiority (31). The ARISE trial represents a further step, targeting the pediatric valve replacement using decellularized aortic homografts (32).…”
Section: Discusionsmentioning
confidence: 99%
“…At the current time, the in situ approach to tissue engineering heart valves has made the most progress with a number of in vivo studies in animals, and with delivery of the valve using transcatheter implantation, showing encouraging results (89,(93)(94)(95). This approach has also been the avenue for the small number of past and present clinicial trials of tissue engineered heart valves, most often employing decellularized homografts for use in the pulmonary valve position (96).…”
Section: In Situ Tissue Engineeringmentioning
confidence: 99%